Effects of Rooting Medium, Light Intensity and Misting on the Root Ability of Shorea Macrophylla Leafy Stem Cuttings - Ting, Sing Teck (2002)
The effects of different proportion of rooting media, hight intensity, and misting on the rooting of leafy stem cuttings of Shorea macrophylla were investigated m Sarawak Indigenous Tree Centre (SITC) The overall rooting percentage of S. macrophylla were 5164% Significant differences (p<0.05) were recorded between nonmist and mist, With non-mist system (55 03%) being better than mist system (48 25%) Cuttings inserted m 12 mixture of sawdust and sand by volume showed higher rooting percentage (57 11 %) than those m different proportion of coconut fibre and sand Rooting percentage is the highest in Ll (control, plastic sheet, 7163%) compared to L2 (1 layer of black netting + plastic sheet, 5813%) and L3 (3 layers of black netting + plastic sheet, 2517%) Higher mortality m L3 may be attributed to the lower photosynthetic rates, which was also associated With low hight intensity received by the treatment The present results suggested that non-mist system Which IS enclosed with a transparent plastic sheet and used rooting medium of different proportion of sawdust and sand IS a practical method to propagate vegetatively S. macrophylla